절사표본 설계에서 비용함수를 고려한 복합추정량 - 심효선; Hyo Seon Sim; 신기일; Key Il Shin (Ŭngyong tʻonggye yŏnʼgu, 2014)
왜도가 심한 사업체 조사에서는 모집단의 일부를 제외하고 표본을 추출하는 방법인 절사표본추출법이 자주 사용된다. 절사층의 경우 표본 관리가 어렵고 조사비용이 많이 들기 때문에 이를 제외한 조사를 실시함으로써 조사의 효율을 높일 수 있다. 그러나 전체 모집단 추정을 위해서는 절사층의 정확한 총합 추정이 매우 중요하다. 최근 Hwang과 Shin (2013)은 Lavallee와 Hidiroglou (1988)가 제안한 LH 알고리즘을 이용하여 표본층을 층화한 후 표본층에서 얻어진 정보와 절사층에서 얻어진 정보를 결합한 복합추정량을 제안하였다. 본 논문에서는 비용함수를 고려한 새로운 표본 설계를 제안하고, 이를 위한 새로운 복합추정량을 제안하였다. 모의실험과 실제 자료 분석을 통하여 본 논문에서 제안한 복합추정량의 우수성을 확인하였다. Cut-off sampling has been widely used for a highly skewed population like a business survey by discarding a part of the population, so called a take-nothing stratum. For a more accurate estimate of the population total, Hwang and Shin (2013) suggested a composite estimator of a take-nothing stratum total that combined the survey results of a take-nothing stratum and a take-some sub-stratum (a part of take-some stratum). In this paper we propose a new cut-off sampling scheme by considering a cost function and a composite estimator based on the proposed sampling scheme. Small simulation studies compared the performances of known composite estimators and the new composite estimator suggested in this study. We also use Briquette Consumption Survey data for real data analysis.